Natural resources and environment management policy : Sri Lanka experience and future directions : a selection of essays - Abeywickrama, Nanda (2018)
On the government policies of Sri Lanka.
Includes bibliographical references.
Keywords: Natural resources -- Sri Lanka -- Management; Natural resources -- Government policy -- Sri Lanka